Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan terhadap Financial Distress pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Fito Saputra; Tartila Devy (ARZUSIN, 2026)
Financial distress is a condition involving a decline in a company’s financial health that may lead to bankruptcy if not properly addressed. Although it has been widely studied, research specifically analyzing the effects of profitability, liquidity, and company size on financial distress among transportation and logistics companies listed on the Indonesia Stock Exchange in the post-COVID-19 pandemic context remains limited. This study aimed to analyze the effects of profitability, liquidity, and company size on financial distress among transportation and logistics companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employed a quantitative approach with a causal research design. The research sample consisted of 25 companies selected through purposive sampling. Data in the form of annual financial statements were collected through documentation and analyzed using panel data regression with the assistance of EViews software. The results showed that profitability, proxied by Return on Equity (ROE), had a significant effect on financial distress, whereas liquidity, proxied by the Cash Ratio, and company size, measured using the natural logarithm (Ln) of total assets, had no significant partial effects. However, simultaneously, profitability, liquidity, and company size had a significant effect on financial distress. These findings strengthen the application of agency theory in explaining the relationship between financial performance and financial distress conditions while extending empirical evidence in Indonesia’s transportation and logistics sector. This study concludes that profitability is the primary factor contributing to the minimization of financial distress risk. Theoretically, this study enriches the literature on the determinants of financial distress, while practically, its findings may serve as a consideration for company management and investors in making financial decisions. Future studies are recommended to include other variables and expand the research objects and period.